The Rostral Mucosa: The Door to Open and Close for Targeted Endoscopic Endonasal Approaches to the Clivus. Issue 3 (26th May 2021) - di Russo, Paolo; Fava, Arianna; Giammattei, Lorenzo; Passeri, Thibault; Okano, Atsushi; Abbritti, Rosaria; Penet, Nicolas; Bernat, Anne-Laure; Labidi, Moujahed; Froelich, Sebastien
Abstract: BACKGROUND: Extended endoscopic endonasal approaches (EEAs) have progressively widened the armamentarium of skull base surgeons. In order to reduce approach-related morbidity of EEAs and closure techniques, the development of alternative strategies that minimize the resection of normal tissue and alleviate the use of naso-septal flap (NSF) is needed. We report on a novel targeted approach to the clivus, with incision and closure of the mucosa of the rostrum, as the initial and final step of the approach. OBJECTIVE: To present an alternative minimally invasive approach and reconstruction technique for selected clival chordomas. METHODS: Three cases of clival chordomas illustrating this technique are provided, together with an operative video. RESULTS: The mucosa of the rostrum is incised and elevated from the underlying bone, as first step of surgery. Following tumor resection with angled scope and instruments, the mucosa of the sphenoid sinus (SS) is removed and the tumor cavity and SS are filled with abdominal fat. The mucosal incision of the rostrum is then sutured. A hangman knot is prepared outside the nasal cavity and tightened after the first stitch and a running suture is performed. CONCLUSION: We propose, in this preliminary report, a new targeted approach and reconstruction strategy, applying to EEAs the classic concept of skin incision and closure for transcranial approaches. With further development in the instrumentations and visualization tools, this technique may become a valuable minimally invasive endonasal approach for selected lesions.